Improvement of P Use Efficiency and P Balance of Rice–Wheat Rotation System According to the Long-Term Field Experiments in the Taihu Lake Basin - Xiao, Liang; Chen, Guanglei; Wang, Hong; Li, Yixuan; Li, Chi; Cheng, Liang; Wu, Wenge; Xiao, Xin; Zhu, Yiyong (Frontiers in Environmental Science, 2022)
Phosphorus (P) accumulation in rice-wheat rotation fields around the Yangze River Delta are enriched during the last decades. To protect environment and save P resource, we conducted field experiments to optimize the P application scheme. First, one field experiment was designed as a series of P fertilizer application doses of 0~100 kg P2O5 hm-2. Grain yield and P uptake by crops were analyzed to calculate P surplus and P use efficiency. Soil P fractions were extracted and tested. According to the P balanc, we optimized fertilization by reducing chemical P amount, which was used by local farmers, and further by substituting chemical P with organic fertilizer. To verify these managements, another field experiment was conducted with five treatments: no N, P, or K fertilizer (CK), only no P fertilizer (NK), farmers' fertilization of P (90 kg P2O5 hm-2) (FFP), reducing 20% P (FFP-20%P), reducing 20% P and replacing 20% P by manure (FFPM-36%P). The grain yield was enhanced by increased P fertilizer and reached at a constant level after 75 kg P2O5 hm-2. Moreover, the annual P surplus was balanced around the input of 150 kg P2O5 hm-2. Accordingly, optimization of fertilization (FFP-20%P) and further by replacing of manure (FFPM-36%P) also achieve the equivalent crop yield like FFP treatment (90 kg P2O5 hm-2). Thus, 72~75 kg P2O5 hm-2 application rate is a threshold for production of rice and wheat and P balance. Total P content in soil was enhanced by increased input of P fertilizer and mainly divided in labile Pi and middle stable Pi fractions. Soil Olsen-P content increased by P fertilization accordingly. While the content of organic P and stable P content was relatively constant. Reducing P fertilizer by 20% had a similar results of soil P fractions, when compared with farmers’ P fertilization treatment. Therefore, reducing at the least 20% current input of P by farmers (annual 180 kg P2O5 hm-2) according to the balance of P surplus in rice and wheat rotation systems is an imperative measure to guarantee crop production with enhanced P use efficiency, and meanwhile can alleviate environmental risk.